2012
DOI: 10.1155/2012/196853
|View full text |Cite
|
Sign up to set email alerts
|

A Thermostable Crude Endoglucanase Produced byAspergillus fumigatusin a Novel Solid State Fermentation Process Using Isolated Free Water

Abstract: Aspergillus fumigatus was grown on chopped wheat straw in a solid state fermentation (SSF) process carried out in constant presence of isolated free water inside the fermentation chamber. The system allowed maintaining a constant vapor pressure inside the fermentor throughout the fermentation process. Crude endoglucanase produced by A. fumigatus under such conditions was more thermostable than previously reported enzymes of the same fungal strain which were produced under different conditions and was also more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
(43 reference statements)
2
14
0
Order By: Relevance
“…The endoglucanase from mutant 60(5) was comparatively more thermostable as it showed t½ of 14.83 min at 60 C which was 4 folds higher than parental strain. These results were also supported by study conducted by [30]and reported the t½of endoglucanases from parental A. oryzae strain was 2 min at 56 C. However, the half-lives of endoglucanase isolated from Aspergillus fumigatus was comparatively higher with t½of 6930, 866 and 36 min at 60 C, 70 C and 80 C, respectively [9]. After incubating the enzyme at higher temperature for extended time and cooling, the irreversible unfolding and reversible inactivated state can be analysed by T m and t½ [49].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The endoglucanase from mutant 60(5) was comparatively more thermostable as it showed t½ of 14.83 min at 60 C which was 4 folds higher than parental strain. These results were also supported by study conducted by [30]and reported the t½of endoglucanases from parental A. oryzae strain was 2 min at 56 C. However, the half-lives of endoglucanase isolated from Aspergillus fumigatus was comparatively higher with t½of 6930, 866 and 36 min at 60 C, 70 C and 80 C, respectively [9]. After incubating the enzyme at higher temperature for extended time and cooling, the irreversible unfolding and reversible inactivated state can be analysed by T m and t½ [49].…”
Section: Discussionsupporting
confidence: 79%
“…Endoglucanases are the largest groups of enzymes constituting third group of enzyme world-wide and used commercially for more than 30 years [9]. Cellulases are used in various industrial applications such as alcohol production, fruits and vegetables extraction, brewing and malting [10], animal feed, food, paper and pulp, textile and laundry industries, agriculture and even for academic and research purposes [11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the variation of entropy is positive due to an increase in disorder, while low values of Δ S ( d ) suggest the exposure of nonpolar side chains which causes the order of water molecules in the form of clathrates or cages [39]. The positive change in entropy of denaturation was above 200 J/(mol·K) which is less than the reported value for an endoglucanase from A. fumigatus [26] which is in the range of 400 J/(mol·K) and very different from the values obtained for a carboxymethylcellulase from A. niger , situated between −200 and −210 J/(mol·K) [39], and for a β -glucosidase from F. solani , with values around −170 J/(mol·K) [40]. …”
Section: Resultsmentioning
confidence: 99%
“…The enzyme activity was measured and residual activity was confirmed after 24 hr treatment at 40°C. The thermostability of PgaB was analyzed by the Arrhenius plot (Siddiqui, Saqib, Rashid, & Rajoka, 2000) and half-lives (T 1/2 ) of PgaB at different temperatures were calculated according to a previous report (Saqib et al, 2012).…”
Section: Determination Of the Effects Of Temperature And Ph On The mentioning
confidence: 99%